Two-dimensional Monte Carlo simulations on transition of aggregate structures of a suspension composed of cubic hematite particles - Akira SATOH; Kazuya OKADA (Nihon Kikai Gakkai ronbunshu, 2015)
We have investigated transition of aggregate structures of a suspension composed of cubic hematite particles in the situation of thermodynamic equilibrium. Monte Carlo simulations have been carried out in order to investigate the dependence of the transition of aggregate structures on the magnetic field strength for various cases of the magnetic particle-particle interaction strength. From the viewpoint of applying a magnetic particle suspension to a surface changing technology, we here consider a two-dimensional system of the cubic hematite particles. Radial distribution functions and order parameters are used for quantitatively discussing in the present results. The main results obtained here are summarized as follows. The cluster formation of magnetic particles significantly appears for a strong magnetic interaction larger than a certain value. In a weak applied magnetic field, the particles tend to aggregate to form thin chain-like clusters if the magnetic particle-particle interaction is relatively small. If the magnetic field is increased, these thin chain-like clusters become thick chain-like clusters. In no external magnetic field, the particles tend to aggregate to form clusters that have large grid-like structures if the magnetic particle-particle interaction is sufficiently large. If the magnetic field is increased, these clusters become thicker chain-like clusters with these grid-like structures. This clearly implies that an applied magnetic field induces the transition of aggregate structures in a cubic hematite particle suspension.